PEMANFAATAN MEDIA VIDEO PADA MATERI PERANG BADAR DALAM PEMBELAJARAN SKI UNTUK MENINGKATKAN KETERTARIKAN BELAJAR SISWA MI - Salsabila Abni; Indriyani, Ita; Intan Shelomitha; Andin Oktovania Ramadhani; Rio Andriyan; M. Nizar Ramdhani; Dian Rif'iyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of video media in the topic of the Battle of Badr in Islamic Cultural History (SKI) learning to enhance students’ learning interest in Madrasah Ibtidaiyah. The research employs a literature review method by examining various scientific sources such as journals, articles, and books related to the topic. The findings indicate that SKI learning still encounters challenges, particularly low student interest due to less varied and teacher-centered instructional methods. The use of video media is considered effective in increasing students’ attention, motivation, and participation, as well as in presenting historical events in a more concrete and understandable manner. Furthermore, video media is also effective in conveying educational values contained in the Battle of Badr, such as courage, faith, and cooperation. Therefore, video media plays a significant role in improving students’ learning interest and making SKI learning more engaging and meaningful.